2009
DOI: 10.1007/s11251-008-9089-y
|View full text |Cite
|
Sign up to set email alerts
|

Searching the Web to learn about a controversial topic: are students epistemically active?

Abstract: Students are making an increased use of the Web as a source for solving information problems for academic assignments. To extend current research about search behavior during navigation on the Web, this study examined whether students are able to spontaneously reflect, from an epistemic perspective, on the information accessed, and whether their epistemic metacognition is related to individual characteristics, such as prior knowledge of the topic and the need for cognition. In addition, we investigated whether… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
93
0
1

Year Published

2011
2011
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 113 publications
(98 citation statements)
references
References 71 publications
4
93
0
1
Order By: Relevance
“…In these multiple document processing (MDP) tasks, participants are asked to process multiple documents, to find, evaluate, and integrate, information from across those documents. Indeed, Mason, Boldrin, and Ariasi (2011, 2010a, 2010b) adapted this approach, using a dummy search interface to display a set of pre-selected documents to students in a 'search-like' interface. Therefore, there has been relatively little work on information seeking in more open contexts, such as the web.…”
Section: Information Seeking Credibility Assessment Behavioursmentioning
confidence: 99%
See 1 more Smart Citation
“…In these multiple document processing (MDP) tasks, participants are asked to process multiple documents, to find, evaluate, and integrate, information from across those documents. Indeed, Mason, Boldrin, and Ariasi (2011, 2010a, 2010b) adapted this approach, using a dummy search interface to display a set of pre-selected documents to students in a 'search-like' interface. Therefore, there has been relatively little work on information seeking in more open contexts, such as the web.…”
Section: Information Seeking Credibility Assessment Behavioursmentioning
confidence: 99%
“…Some of this research has further utilized think-aloud protocols to gather epistemic data, notably that of Boldrin and Ariasi (2011;2010a, 2010b who find that students do spontaneously reflect on epistemic concerns in information seeking while using a 'dummy' search interface (designed to return a preselected set of documents). Additional work in online information seeking contexts suggests that students with more "evaluative stances" on psychometric measures are more likely to meaningfully evaluate websites, with integration and critical evaluation of multiple online sources more likely of those with more sophisticated perspectives on the "multiplicity of knowledge" (Barzilai & Zohar, 2009.…”
Section: Introductionmentioning
confidence: 99%
“…By offering abundant and diverse information, the Web-based learning environment enables students not only to access up-to-date information but also to seek information of their own interests. Researchers agree that integration of the Web into science teaching and learning can promote students' conceptual understanding (Butler and Lumpe 2008;ChanLin 2008;Hoffman et al 2003;Wu and Tsai in press) as well as help development of evaluation skills (Mason et al 2009;Tsai 2004aTsai , 2008a if the activity is planned properly. However, many studies (Dias et al 1999;Halverson et al 2010;Kuiper et al 2005) have shown that people of all ages often encounter difficulties (e.g., specifying terms or feeling disoriented) while seeking information online.…”
Section: Introductionmentioning
confidence: 99%
“…Of particular interest, recent research on epistemic beliefs has shown that beliefs influence cognitive and metacognitive processing (Hofer 2004;Mason et al 2010;Muis 2008;Muis and Franco 2010;Pieschl et al 2008;Richter and Schmid 2010;Strømsø and Bråten 2010). Typically, researchers exploring relations between epistemic beliefs and metacognition have found that "sophisticated beliefs" (e.g., knowledge is tentative, changing, complex, and constructed) are associated with more metacognitive strategy use.…”
mentioning
confidence: 99%